RESPONSIBILITY IN THE EMPLOYMENT RELATIONSHIP: DISTINCTIVE FEATURES OF DISCIPLINARY LIABILITY IN THE GENERAL AND SPECIAL EMPLOYMENT RELATIONS REGIME: 1. О дисциплинској одговорности – уводна разматрања; 2. Концепт дисциплинске одговорности и дисциплинског поступка – критички осврт на општи режим радних односа; 3. Особености дисциплинске одговорности у посебном режиму радних односа- Закон о државним службеницима; Закључне напомене - Perić, Slobodanka P (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
Establishing the employment relationship involves acquiring, i.e. assuming certain rights, duties and responsibilities for both parties in the employment relationship, in accordance with the law, the collective agreement, the employer’s bylaws, and the employment contract. The employment relationship involves not only rights and duties, but also the responsibility. Responsibility can be of a legal and non-legal nature. Legal responsibility is of greater importance for the employees. On the whole, legal responsibility may be disciplinary, material, administrative misdemeanor, economic offense and criminal in nature. The subject matter of labor law includes only disciplinary and material responsibility of the employee, while other types of legal responsibility are the subject of other legal disciplines. Although the former labor legislation of the Republic of Serbia regulated the disciplinary responsibility of the employees in detail, such practice has been completely abandoned within the new labor legislation and amounts to a summary dismissal procedure. Unlike Labor Law, Law on Civil Servants contains numerous provisions on the disciplinary and material responsibility of civil servants. In addition, this law regulates procedural issues regarding the rules for initiating and conducting a disciplinary procedure, including disciplinary sanctions in or removing them from the personnel files, etc. In this paper, the author analyzes disciplinary responsibility, through the specifics of substantive and procedural norms for its establishment in the general and the special regime of the employment relationship, and by critical analysis, from the aspect of the rule of law, considers the justification of such legislative solutions.